The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7150/jca.46343
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic, clinicopathologic, therapeutic and prognostic value of Plasma Heat Shock Protein 90 levels in patients with advanced Gastrointestinal Carcinoma

Abstract: Purpose: Heat shock protein 90 (HSP90) is a critical molecular chaperone for protein folding, intracellular disposition and regulation of tumor biological behavior in the extracellular space. HSP90 has received much attention due to its specific effect in gastrointestinal cancer. This clinical study sought to determine whether HSP90 in plasma may serve as a biomarker in patients with advanced gastrointestinal carcinoma. Methods: Using human plasma samples of advanced gastrointestinal carcinoma, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Previously studies have showed that plasma HSP90α is an excellent biomarker for the diagnosis of lung cancer and liver cancer ( Jhaveri et al, 2014 ; Shi et al, 2014 ; Fu et al, 2017 ). Meanwhile, plasma HSP90α levels were significantly higher than healthy controls in other cancers, but the diagnostic efficiency was insufficient, such as gastric cancer, breast cancer, nasopharyngeal carcinoma and colorectal cancer ( Kasanga et al, 2018 ; Liu et al, 2019 ; Lin et al, 2020 ; Zhang et al, 2020 ). In current study, the plasma HSP90α levels was significantly higher in CRC patients than in healthy controls and consistent with previously reported results ( Kasanga et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously studies have showed that plasma HSP90α is an excellent biomarker for the diagnosis of lung cancer and liver cancer ( Jhaveri et al, 2014 ; Shi et al, 2014 ; Fu et al, 2017 ). Meanwhile, plasma HSP90α levels were significantly higher than healthy controls in other cancers, but the diagnostic efficiency was insufficient, such as gastric cancer, breast cancer, nasopharyngeal carcinoma and colorectal cancer ( Kasanga et al, 2018 ; Liu et al, 2019 ; Lin et al, 2020 ; Zhang et al, 2020 ). In current study, the plasma HSP90α levels was significantly higher in CRC patients than in healthy controls and consistent with previously reported results ( Kasanga et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a series of clinical and retrospective analyses have drawn opposing conclusions on the correlation between HSP90α and the prognosis of patients with tumors. For example, Zhang et al 26 found that HSP90α was highly expressed in the peripheral blood of 103 patients with gastric cancer and 83 patients with colorectal cancer, but was not related to the PFS and OS of the patients, whereas in breast cancer, serum HSP90α levels were negatively correlated with OS. 27 , 28 Chen 29 et al compared the expression level of HSP90 in the serum of 137 patients with advanced lung cancer treated with immunotherapy with the PFS and OS of the patients and found that the patients in the high-level group of HSP90α had worse PFS and OS than those in the low-level group.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of eHsp90 have been found to correlate with metastatic potential in prostate cancer cell lines ( Hance et al, 2012 ). Plasma Hsp90 has been developed as a biomarker in liver cancer for diagnosis as well as to evaluate efficacy of therapeutic interventions and is also elevated in advanced gastrointestinal malignancies ( Fu et al, 2017 ; Zhang Y. et al, 2020 ; Wei et al, 2020 ). Additionally, plasma levels of Hsp90α are elevated in patients with malignant tumors compared to controls or those with benign tumors and are further elevated in those with metastatic breast cancer compared to localized disease ( Wang et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%